Diagnosing and Treating the Causes of Women’s Polycystic Ovary Syndrome: Clinical and Prospective Study - Souad Fareg Mohammed Dadoush (African Journal of Advanced Pure and Applied Sciences, 2023)
This article aims to identify the methods of diagnosis and treatment of the causes of women’s polycystic ovary syndrome: Clinical and prospective study. One hundred and twenty – three women were medically diagnosed by both medical laboratory tests and ultrasound image machines. Moreover, a questionnaire was designed to question 25 specialized obstetricians and gynecologists to provide answers based on their practising and experience, regarding the methods of diagnosis, symptoms of polycystic ovary syndrome, causes and approved treatment methods for women with polycystic ovary syndrome. Data analysis using statistical program for social sciences (SPSS version 24). A descriptive and Analytical approach was adopted. The study concluded that 37% of the women with polycystic ovary syndrome aged from (20 to less than 40 years), and 59% of the women with polycystic ovary syndrome were found at weights ranging from (over 65 kg). The study indicated that diabetic patients (DN) were the higher percent of women with Polycystic Ovary Syndrome (29%), followed by women with heart disease (18%), followed by women with HTN (15%), followed by women with ASTHMA diseases (8%), followed by the women with ANEMIA diseases (7%). An irregular menstrual period, the appearance of acne, especially in the neck and armpits, oily skin, increased hair growth on the face, chest, or thighs, dark spots and thickening of the skin, head hair loss, hair on the face and body, overweight, and density hair on the face and body infertility are the main symptoms of polycystic ovary syndrome with (68%). The hormonal imbalances, insulin resistance, genetics, inflammation, hyperanrdogenism, anovulation, and infertility are the root causes of polycystic ovary syndrome (80%). HBA1C: cumulative sugar, prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FH), testosterone, and estrogens are the core methods to diagnose women with polycystic ovarian syndrome. Lifestyle, medication, Assisted Reproductive Technology (ART), and psychological support were approved by the experts in this field as the main methods of polycystic ovary syndrome treatment (72%).